Mayo Registry for Telemetry Efficacy in Arrest (MR TEA) study: An analysis of code status change following cardiopulmonary arrest. (July 2015) - Snipelisky, David; Ray, Jordan; Matcha, Gautam; Roy, Archana; Chirila, Razvan; Maniaci, Michael; Bosworth, Veronica; Whitman, Anastasia; Lewis, Patricia; Vadeboncoeur, Tyler; Kusumoto, Fred; Burton, M. Caroline
Abstract: Introduction: Code status discussions are important during a hospitalization, yet variation in its practice exists. No data have assessed the likelihood of patients to change code status following a cardiopulmonary arrest. Methods: A retrospective review of all patients that experienced a cardiopulmonary arrest between May 1, 2008 and June 30, 2014 at an academic medical center was performed. The proportion of code status modifications to do not resuscitate (DNR) from full code was assessed. Baseline clinical characteristics, resuscitation factors, and 24-h post-resuscitation, hospital, and overall survival rates were compared between the two subsets. Results: A total of 157 patients survived the index event and were included. One hundred and fifteen (73.2%) patients did not have a change in code status following the index event, while 42 (26.8%) changed code status to DNR. Clinical characteristics were similar between subsets, although patients in the change to DNR subset were older (average age 67.7 years) compared to the full code subset (average age 59.2 years; p  = 0.005). Patients in the DNR subset had longer overall resuscitation efforts with less attempts at defibrillation. Compared to the DNR subset, patients that remained full code demonstrated higher 24-h post-resuscitation ( n  = 108, 93.9% versus n  = 32, 76.2%; p  = 0.001) and hospital ( n  = 50, 43.5% versus n  = 6, 14.3%; p  = 0.001) survival rates. Patients in the DNR subset were more likely to have neurologic deficits on discharge and shorter overall survival. Conclusions: Patient code status wishes do tend to change during critical periods within a hospitalization, adding emphasis for continued code status evaluation.